1980
DOI: 10.1097/00000658-198002000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Blood Flow at Various Intraluminal Pressures in the Piglet with Closed Abdomen

Abstract: The influence of intraluminal pressure on intestinal blood flow was studied in two segments of the small intestine and two of large intestine ligated after insertion of intraluminal catheters in ten piglets. Intestinal segments were inflated in stepwise increments in intraluminal pressures of 15, 30, 45 and 60 mmHg and blood flow was measured with radioactive microspheres using four isotopes (Ce, Cr, Sr, Sc). Other segments were inflated to a pressure of 60 mmHg and then pressure decreased in a stepwise fashio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

1984
1984
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 7 publications
0
23
0
2
Order By: Relevance
“…In 14 other animals (aged 2 weeks and 1 month), an artery supplying the jejunum and one supplying the ileum were exposed through a ventral midline incision, an electromagnetic flow transducer was placed around each vessel, and the incision was closed with wound clips. All animals were given atro pine (0.5 mg/kg every hour) to minimize the effects of intestinal intraluminal pressure on blood flow [23]. Intestinal vascular resistance (MVR for entire intes tine.…”
Section: Procedures For the Intestinal Circulation Studiesmentioning
confidence: 99%
“…In 14 other animals (aged 2 weeks and 1 month), an artery supplying the jejunum and one supplying the ileum were exposed through a ventral midline incision, an electromagnetic flow transducer was placed around each vessel, and the incision was closed with wound clips. All animals were given atro pine (0.5 mg/kg every hour) to minimize the effects of intestinal intraluminal pressure on blood flow [23]. Intestinal vascular resistance (MVR for entire intes tine.…”
Section: Procedures For the Intestinal Circulation Studiesmentioning
confidence: 99%
“…The lesions were enlarged by the reduction in the blood flow of the microcirculation caused by distention of the colon 12. However, infusion of a foreign substance into the microcirculation of the colon in animals may not reflect the process of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in arterial blood flow is a direct result of small bowel obstruction. A negative correlation exists between bowel diameter, intraluminal pressure, and blood flow [18][19][20], Strodahl et al [ 18] showed a decreased blood flow to 10% of normal values in a closed loop guinea pig bowel prepa ration after contrast medium injection. The appearance of Gastrografin in the urinary tract has been considered a sign of a break in the intestinal mucosa, as proven in experimental animal models [21].…”
Section: Discussionmentioning
confidence: 99%